A review of fluid and hydration in competitive tennis - Kovacs, M. S. (International Journal of Sports Physiology and Performance, 2008)
Hypohydration is known to impair performance and increases the risk of heat injury. Therefore, the consumption of appropriate fluid volumes before, during, and after tennis play is important to maintain physiological homeostasis and performance. Tennis is a sport that typically has points lasting fewer than ten seconds, with short-to-moderate rest periods between each work bout. This sequence is repeated over hours. Most fluid and hydration research has focused on continuous aerobic exercise, which provides vastly different physiological strain compared with tennis practice and competition. Consequently, practical recommendations on maintaining hydration status for aerobic continuous exercise may not be appropriate for tennis athletes. Tennis players can sweat more than 2.5 L·h-1 and replace fluids at a slower rate during competition than in practice. In warm and hot environments, electrolyte-enhanced fluid should be consumed at greater than >200 mL per changeover and ideally closer to 400 mL per changeover. Tennis scientists, coaches, and players need to individualize hydration protocols to arrive at the optimal hydration strategy.